2015
DOI: 10.3174/ajnr.a4600
|View full text |Cite
|
Sign up to set email alerts
|

A Spiral Spin-Echo MR Imaging Technique for Improved Flow Artifact Suppression in T1-Weighted Postcontrast Brain Imaging: A Comparison with Cartesian Turbo Spin-Echo

Abstract: BACKGROUND AND PURPOSE:A challenge with the T1-weighted postcontrast Cartesian spin-echo and turbo spin-echo brain MR imaging is the presence of flow artifacts. Our aim was to develop a rapid 2D spiral spin-echo sequence for T1-weighted MR imaging with minimal flow artifacts and to compare it with a conventional Cartesian 2D turbo spin-echo sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 11 publications
(8 reference statements)
0
39
0
Order By: Relevance
“…24 Studies have shown the usability of spiral imaging in T1-weighted spin echo sequences. 25 Recently, it has been demonstrated that spiral imaging can be used to generate TOF-MRA sequences in a comparable amount of time when compared to TOF-MRA accelerated by compressed sensing. 26 Due to the inherent advantages of spiral imaging mentioned above, we hypothesize that it can markedly accelerate TOF-MRA, thereby outperforming other acceleration algorithms such as TOF-MRA accelerated by compressed sensing, with only minor drawbacks regarding coverage, spatial resolution, or diagnostic quality.…”
Section: Introductionmentioning
confidence: 99%
“…24 Studies have shown the usability of spiral imaging in T1-weighted spin echo sequences. 25 Recently, it has been demonstrated that spiral imaging can be used to generate TOF-MRA sequences in a comparable amount of time when compared to TOF-MRA accelerated by compressed sensing. 26 Due to the inherent advantages of spiral imaging mentioned above, we hypothesize that it can markedly accelerate TOF-MRA, thereby outperforming other acceleration algorithms such as TOF-MRA accelerated by compressed sensing, with only minor drawbacks regarding coverage, spatial resolution, or diagnostic quality.…”
Section: Introductionmentioning
confidence: 99%
“…Spiral MRI promises many benefits including high acquisition and SNR efficiency, short minimum echo‐times, robustness to motion and flow, and higher geometric fidelity (compared to EPI). In the past few years, spiral has been shown to provide unique capabilities or substantial advantages over conventional imaging in post‐Gad T 1 weighted imaging, 3D TSE imaging, cardiac flow imaging, diffusion weighted imaging, real‐time imaging, perfusion imaging, functional MRI, MR fingerprinting, and many other applications. Despite its potential and long history, spiral MRI has struggled to find widespread clinical adoption, in large part due to artifacts from susceptibility‐induced field inhomogeneity and eddy current‐induced gradient errors.…”
Section: Introductionmentioning
confidence: 99%
“…While the current work explores the use of in‐plane radial sampling, efficiency of the pulse sequence could be further improved using alternative non‐Cartesian trajectories such as spiral, GRASE or bent radial readout schemes . These trajectories would allow the acquisition of sufficient k‐space samples in a single shot, reducing further the scan time.…”
Section: Discussionmentioning
confidence: 99%